PENGGUNAAN ALAT PERAGA PINANG GEBE PADA MATERI PERKALIAN DAN PEMBAGIAN DI SEKOLAH DASAR NABIRE - Bin Alit, Indra Fitria Ningsih; Yektiningtias, Wigati; Tanto; Imawan, Okky Riswandha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the use of Pinang gebe teaching aids in mathematics learning, specifically for multiplication and division in fourth-grade students at SD Negeri Inpres 01 Kalisemen. Mathematics is often considered an abstract and difficult subject for elementary school students, requiring concrete media or teaching aids that are familiar to the students' environment (an ethnomathematics approach). This study employed a qualitative approach with a descriptive research style. The subjects consisted of two classroom teachers and 42 students. Data collection was conducted through observation of learning activities, in-depth interviews with teachers and students, and documentation. Data analysis techniques used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the use of Pinang gebe teaching aids significantly concretized the concept of multiplication as repeated addition and division as repeated subtraction. These teaching aids, made from local natural materials, were proven effective in increasing students' enthusiasm, engagement, and understanding of mathematical concepts by integrating contextual objects familiar to their daily lives. Although there were minor obstacles such as time management when distributing teaching aids, these were effectively addressed through classroom management by the teacher. The conclusion of this study is that the Pinang gebe teaching aid can be an alternative learning medium based on local wisdom that significantly supports the learning process of basic arithmetic operations in elementary schools.